Forecasting bond returns using asymmetric regression and investment management - Kanapeckas, Jonas (Nonlinear Analysis: Modelling and Control, 1998)
The first section of this research formulates the forecasting task important for managing investment portfolio as well as discusses certain statistical data. The second section is devoted to potential regressors frequently used to forecast risk premiums of bonds, this section extensively use the ideas presented in article [4]. The third section includes the research of asymmetry of relation between risk premiums and regressors. The fourth section is devoted to the investigation of applicability received results in practice.